Implementasi metode Design For Six sigma (DFSS) pada kemasan Bumbu Oil Mie Goreng (BOMG) di PT. XZY - Hekmah, Lailatul; Negoro, Yanuar Pandu; Jufriyanto, Moh (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT XZY is a company in the industrial sector that produces instant noodles. In the production process, PT XZY faces several problems that cause product defects, especially in the packaging of Bumbu Oil Mie Goreng (BOMG). This packaging has several deficiencies such as quality defects (squashed packaging, folded edges, contents not up to standard) and unstable productivity. Therefore, this study aims to identify the factors that affect product defects and conduct development to improve quality and productivity. This research uses the Design for Six Sigma (DFSS) method with the stages of Define, Measure, Analyze, Design (DMAD). Based on the results of research using the design from six sigma method, it states that the highest sigma value of defects occurs with a total sigma value of 2,910 and also produces the highest value of defects in the noodle packaging squash factor of 38% resulting from the Pareto diagram.